Impact of Innovative Learning in Mathematics and Natural Sciences on Student Learning Achievements: A Meta-Analysis - Niza; Slamet Suyanto (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2023)
This study was to analyze the impact of innovative learning on student learning achievement in Mathematics and Natural Sciences from 2014 until 2021. The data collection method used in this study is a meta-analysis, where the researchers would search related articles through Google Cendekia (Google Scholars) and ScienceDirect. This research obtained 227 articles. All selected articles cover the research conducted in schools, from elementary to high school level. These articles will be analyzed in several steps: (1) determining research domains that will be summarized; (2) selecting the types of collected publications; (3) collecting results of studies or literature; (4) listing research data; (5) calculating the effect size of each source or study. After passing this five-step process, 21 articles that discussed how innovative learning in mathematics and natural sciences affects student achievement were selected. These articles will be analyzed using the JAMOVI application. The results found an average difference, ranging from -0.99 to 3.10. Keywords:  Innovative Learning, Natural Sciences, Learning Achievements